Molecular analysis of the Retinoic Acid Induced 1 gene (RAI1) in patients with suspected Smith-Magenis syndrome without the 17p11.2 deletion. - Thierry Vilboux (PLoS ONE, 2011)
Smith-Magenis syndrome (SMS) is a complex neurobehavioral disorder characterized by multiple congenital anomalies. The syndrome is primarily ascribed to a ∼3.7 Mb de novo deletion on chromosome 17p11.2. Haploinsufficiency of multiple genes likely underlies the complex clinical phenotype. RAI1 (Retinoic Acid Induced 1) is recognized as a major gene involved in the SMS phenotype. Extensive genetic and clinical analyses of 36 patients with SMS-like features, but without the 17p11.2 microdeletion, yielded 10 patients with RAI1 variants, including 4 with de novo deleterious mutations, and 6 with novel missense variants, 5 of which were familial. Haplotype analysis showed two major RAI1 haplotypes in our primarily Caucasian cohort; the novel RAI1 variants did not occur in a preferred haplotype. RNA analysis revealed that RAI1 mRNA expression was significantly decreased in cells of patients with the common 17p11.2 deletion, as well as in those with de novo RAI1 variants. Expression levels varied in patients with familial RAI1 variants and in non-17p11.2 deleted patients without identified RAI1 defects. No correlation between SNP haplotype and RAI1 expression was found. Two clinical features, ocular abnormalities and polyembolokoilomania (object insertion), were significantly correlated with decreased RAI1 expression. While not significantly correlated, the presence of hearing loss, seizures, hoarse voice, childhood onset of obesity and specific behavioral aspects and the absence of immunologic abnormalities and cardiovascular or renal structural anomalies, appeared to be specific for the de novo RAI1 subgroup. Recognition of the combination of these features will assist in referral for RAI1 analysis of patients with SMS-like features without detectable microdeletion of 17p11.2. Moreover, RAI1 expression emerged as a genetic target for development of therapeutic interventions for SMS.